Development of Rural Tourism With Methods Based on Segmentation Through the Example of Alsó-Ipoly Mente - Kóródi, Márta; Dr Mondok, Anita (Jelenkori Társadalmi és Gazdasági Folyamatok, 2023)
The peculiarities of the Lower Ipoly can be seen in its territorial location (on the border), rural and at the same time close to the capital, in its diverse landscape features (river valley, the western slopes of the Börzsöny, partly in the Danube-Ipoly National Park area), which can provide a suitable development basis from a tourism point of view. The study uses the conclusions of a preliminary survey of the region’s consumer and organizational market to determine the emerging types of rural tourism and narrow it down to those that play a potentially significant role based on their features and development potential. The tourism product development program packages that target well-defined tourist segments, differentiated in space and time, according to their ranking of importance (primary, secondary, tertiary) have been identified. The planned developments based on the established segments can be taken into account on the one hand as the basis for projects that can be implemented in different time periods, and on the other hand, they also provide an opportunity to create a differentiated, yet connected, modular product range.